"BODY THEATER BUTOH: A REVIEW OF TATSUMI HIJIKATA AND KAZUO OHNO" - Aji, Ahmad Wahyu; S.Sn., M.Si, Dr. autar abdillah (APRON Jurnal Pemikiran Seni Pertunjukan, 2024)
Body theater is a process of physical training with body awareness as the idea or the body itself as the concept for the training process. Body theater offers a new perspective on the body, not merely as a means of expression but as an identity itself. Butoh is a form of theater originating from Japan, created from the creative thoughts of two maestros, Tatsumi Hijikata and Kazuo Ohno. It was intended as a form of protest against the Japanese government because many young people died senselessly on the battlefield. The concept of Butoh encompasses death and how to see death as beauty. This underpins the researcher’s intention to delve deeper. Based on this study, the researcher formulates the problems in the research as follows: (1) The Form of Body Theater in Butoh Performances, (2) Body Theater in the Butoh of Tatsumi Hijikata and Kazuo Ohno. The aim of this research is to provide a new reference study on Butoh performances, to offer written information to Butoh body theater enthusiasts, and to understand the form of Butoh body theater by Tatsumi Hijikata and Kazuo Ohno. This research uses qualitative methods based on a descriptive approach with data sources from papers (writings). Data collection techniques utilize existing and relevant literature sources. Data reduction and data presentation are used as the basis for data analysis with data validity consisting of source triangulation, technique triangulation, and method triangulation. The results and discussion of this research show that Butoh is a form of Japanese body theater that encompasses various activities, techniques, and motivations for movement. After World War II, Butoh emerged in 1959 through the collaboration between its two main founders, Tatsumi Hijikata and Kazuo Ohno. The term means ’dance of darkness,’ and its form is built on a vocabulary of ’harsh physical movements and rough habits.’ Keywords: Body Theater, Butoh, Kazuo Ohno, Tatsumi Hijikata